PsycEXTRA Dataset 1992
DOI: 10.1037/e730502011-001
|View full text |Cite
|
Sign up to set email alerts
|

Lower BAC Limits for Youth: Evaluation of the Maryland .02 Law: Technical Summary

Abstract: Evaluation of the Maryland .02 Law 6' perler"t'"t 0rt•n'ast'M Cede

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…156 Of note, a combined media and enforcement campaign in 2 Maryland counties after enactment of a zero-tolerance law in that state yielded greater awareness of the law and a one third greater decrease in alcohol-related crashes among people Ͻ21 years of age in those counties, compared with the rest of the state. 157 Other programs may also be effective in reducing the prevalence of teen drinking and driving. Systematic reviews of the relevant research literature found that sobriety checkpoints and mass media campaigns 158 can reduce rates of alcohol-related traffic crashes.…”
Section: Adolescent Drinking and Drivingmentioning
confidence: 99%
“…156 Of note, a combined media and enforcement campaign in 2 Maryland counties after enactment of a zero-tolerance law in that state yielded greater awareness of the law and a one third greater decrease in alcohol-related crashes among people Ͻ21 years of age in those counties, compared with the rest of the state. 157 Other programs may also be effective in reducing the prevalence of teen drinking and driving. Systematic reviews of the relevant research literature found that sobriety checkpoints and mass media campaigns 158 can reduce rates of alcohol-related traffic crashes.…”
Section: Adolescent Drinking and Drivingmentioning
confidence: 99%
“…Possession and purchase laws have continued to have an effect up through 2012, but not as much as in the earlier years of adoption. Use-and-lose (-7.9%) and zero-tolerance (-2.9%) laws have also been shown in other studies to be effective on underage drinking drivers (Blomberg, 1992;Fell et al, 2009;Voas et al, 2003). The requirement that bartenders be at least age 21 (-4.1%) had an effect, whereas the ages of sellers and servers did not.…”
Section: Discussionmentioning
confidence: 90%
“…Zerotolerance and "sort of" zero-tolerance laws ranging from 0.00 to 0.02 g/dL for youth have proved effective in reducing the number of fatal crashes involving underage drinking drivers (Fell & Voas, 2006a). Also see Blomberg (1992), Lacey, Jones, and Wiliszowski (2000) and Hingson, Howland, Heeren, and Winter (1992). In a follow-up study, Hingson, Heeren, and Winter (1994) compared 12 states that adopted zero tolerance for youth before 1991 with 12 comparison states that did not lower their BAC levels.…”
Section: Zero Tolerance For Under 21mentioning
confidence: 96%